1989
DOI: 10.1002/jsfa.2740490213
|View full text |Cite
|
Sign up to set email alerts
|

Differences between wines fermented with and without sulphur dioxide using various selected yeasts

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 4 publications
7
36
1
Order By: Relevance
“…Interestingly, the production of 3-ethoxy-1-propanol increased when SO 2 was absent, a result which is consistent with previous works on wines fermented without the use of SO 2 (Herraiz, Martin-Alvarez, Herraiz, & Cabezudo, 1989;Margheri & Versini, 1986;Sonni et al, 2009). Irwin (1992) postulated that the formation of this alcohol may derive from the Ehrlich degradation of O-ethylhomoserine, which is a by-product of the methionine biosynthetic pathway.…”
Section: End Of Fermentationsupporting
confidence: 87%
“…Interestingly, the production of 3-ethoxy-1-propanol increased when SO 2 was absent, a result which is consistent with previous works on wines fermented without the use of SO 2 (Herraiz, Martin-Alvarez, Herraiz, & Cabezudo, 1989;Margheri & Versini, 1986;Sonni et al, 2009). Irwin (1992) postulated that the formation of this alcohol may derive from the Ehrlich degradation of O-ethylhomoserine, which is a by-product of the methionine biosynthetic pathway.…”
Section: End Of Fermentationsupporting
confidence: 87%
“…26 Similar results on the role of SO 2 during alcohol fermentation have been reported by other authors. 21 -23 Conversely, the amounts of other alcohols, such as n-propanol and 3-ethoxy-1-propanol, were higher in wines fermented without SO 2 , as already reported by Herraiz et al 21 and Margheri and Versini. 23 For this class of compound, tannins did not show any appreciable effect.…”
Section: Alcoholssupporting
confidence: 73%
“…29 These results were in contrast with some studies reported in the literature. For example, Herraiz et al, 21 when evaluating the differences between wines fermented with or without sulfur dioxide, found that, if compared with SO 2 -free fermentations, wines fermented with SO 2 were characterised by higher levels of ethyl octanoate, although there were no differences in the amounts of ethyl hexanoate. Similar findings were reported by Margheri and Versini, 23 who also noted that ethyl decanoate was produced at higher concentration in SO 2 -added musts.…”
Section: Estersmentioning
confidence: 97%
“…The main factors a †ecting these products are the yeast species, the must type and fermentation conditions (Suomalainen and Lehtonen 1979 ;Soles et al 1982). These products are released into the fermentation medium and contribute to wine Ñavour, so that wine quality depends on the kind of compounds and concentration at which these are present (Herraiz et al 1989(Herraiz et al , 1990. It has been shown that the main fraction of the aroma compounds is produced during fermentation by yeast.…”
Section: Introductionmentioning
confidence: 99%